(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Coconut is a good source of minerals like manganese, copper, iron and selenium, all of which are important for various bodily functions including bone health and red blood cell formation. Manual dehusking of coconut is labour-intensive, hence, this work focuses on development of an efficient coconut dehusking machine adaptable to Nigerian coconuts for small-scale coconut processors using the lead screw technology that facilitates automatic operation. The machine uses electric motors to drive lead screws, which translate rotational action into linear movement. Effective husk removal is made possible by a tearing force mechanism attached to the lead screws and the machine’s operations are coordinated by an Arduino with a "C" programming. Radio Frequency (RF) module was used to automate the dehusking process. Control action of the RF module activates the rotation of the upper motor while the motion of the lower motor lifts the coconut placed in the coconut holder to the dehusking knife where a tearing force would be exerted on the husk of the coconut. The average time taken to dehusk a coconut was 114 seconds. Compared to the manual method with dehusking time of 513 seconds per coconut, the designed machine has a notable reduction in dehusking time. The success recorded during testing clearly demonstrates its efficacy and would translate to improved productivity and enhanced safety for small-scale farmers and the coconut industry.